EFEKTIFITAS PEMAKAIAN KELAMBU BERINSEKTISIDA DI DESA ENDEMIS MALARIA DI KABUPATEN WONOSOBO - Bina Ikawati; Bambang Yunianto; Rr Anggun Paramita Djati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2010)
This research was conducted in Wonosobo, Central Java with quasi experimental method with treatment and control groups. The treatment group was treated with IBN (Impregnated Bed Net). The results showed that IBN was still effective until 14 weeks with 93,33% death of mosquito test, after IBN usage vector density bitting indoor and resting on the wall in treatment area were decreased but vector density biting outdoor and resting in cage increased. Parousity at treatment area before and after IBN usage decreased from 48,7% to 37,7% while in area control was constant. There was significant difference of knowledge and attitude of people on treatment and control group about malaria whlie the practice was not different. There were some complains on treatment group about the early usage of IBN i.e unpleasant smell, headache, unconvenience but there was no societies rejection about IBN usage.